New reflections on grammaticalization - Wischer, Ilse, 1959-; Diewald, Gabriele (Typological studies in language, 2002)
The contributions in this volume cover a wide range of theoretical and methodological issues and raise a number of new questions that indicate the future direction of grammaticalization studies. The volume focuses on issues such as grammaticalization and lexicalization; the unidirectionality hypothesis; the issue of the relevance of contexts for grammaticalization; the description of grammaticalization paths. Much of the current work concentrates on such categories, as discourse markers, honorifics or classifiers, which have not previously been central to works on grammaticalization. Other stu.